Qualitative Study of the Nutritional Value of Banana Nuggets Based on the Recommended Dietary Allowances and the Indonesian Food Composition Table - Lidyawati Nurhapiza; Tessa Nurul Shahira; Junita Junita; Jasika Jasika; Amy Ledyanna; Uray Dinda Ragista (Journal of Food Security and Agroindustry, 2026)
Crushed bananas are combined with binding agents and flavor enhancers to create banana nuggets, which are then covered with breadcrumbs. Using information from the Indonesian Food Composition Table (TKPI), this study attempts to evaluate the nutritional content of banana nuggets and determine how much they contribute to the Recommended Dietary Allowance (RDA). The caloric, carbohydrate, protein, and fat contents of all the ingredients bananas, wheat flour, tapioca flour, sugar, eggs, milk powder, and cheese were added together and converted to units per 100 grams of product in order to do the quantitative calculation. According to the findings, banana nuggets contain 188.05 kcal of total calories, 35.63 grams of carbohydrates, 5.08 grams of protein, and 3.83 grams of fat per 100 grams. The primary source of energy is carbohydrates, which are mostly found in bananas, wheat flour, and granulated sugar. Banana nuggets are better classified as an energy snack rather than a main meal because the AKG percentage indicates a low contribution to all nutrients. Because it contains protein from eggs, milk powder, and cheese as well as vitamins and minerals, this product still has extra value